The effect of Futsal Training on the Speed, Agility, and Anaerobic Power of Male Children Aged 12-14 Years Old - Akın Balcıoğlu; Bilal Biçer (Türk Spor ve Egzersiz Dergisi)
The present study aimed to investigate the effect of 6-week futsal training on the speed, agility, and anaerobic power of male children aged 12-14 years old. A total of 20 male students from Ayşe Fitnat Middle School voluntarily participated in this study. Their mean age was 13.50±0.51 years, the mean length was 1.61±0.06 meters, the mean weight was 50.23±8.43 kg, and the mean body-mass index was 19.42±2.74 kg/m2. Ten participants were assigned to participate in futsal training, and the other 10 formed a control group. The research was designed as an experiment that included a pre-test and post-test within the control and experimental groups. The experimental group (Futsal) participated in a 6-week futsal training with 3 days a week and an hour a day of practice. To evaluate both groups' physical and motor capacities, length, weight, body-mass index, 20m-sprint test, agility test, vertical jump test, and anaerobic power tests were applied. All statistical analyses were performed by IBM SPSS 23.0 computer program. The level of significance was set as p lt;0.05. There was a statistically significant difference in the experimental group's pre-test and post-test values in the 20 m sprint test, agility, vertical jump, and anaerobic power measurements (p lt;0.05). However, no statistical significance was determined in the control group. Post-test results between the experimental and control groups revealed that the experimental group significantly had better 20 m sprint, agility, and vertical jump scores than the control group (p lt;0.05). Even though there was no significant difference in anaerobic power between the two groups, the experimental group had substantially higher values compared to the control group. As a result, it can be concluded that 6-week futsal training three days a week and an hour a day can improve the speed, agility, and anaerobic power among male children aged between 12 and 14 years old.